PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MELALUI PEMBELAJARAN BERBASIS MASALAH - Fitrianto Eko Subekti (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
This research aims to increase the ability in concept comprehension of the students class XII Farmasi B SMK Muhammadiyah Purwokerto on statistics. It is carried out in three cycles. In which each end of the cycle is carried out on evaluation to measure the ability of the students concept comprehension. The data of the concept comprehension is taken using a test. This data, then showed on a mean form. The result of the evaluation shows that there is an increasing from cycle 1 to cycle II, and from cycle II to cycle III. The mean of cycle I = 70, cycle II = 75 and cycle III = 78. Based on the above result, it can be concluded that throught learning based on problem thr ability in concept comprehension can be increased.